[Laiškas] / Lunkevičius (Łunkiewicz) Jonas Liudvikas, kunigas - Jonui Januškevičiui. - (:unkn) unknown (My University, 1862)
1 laiškas apie plytų ir medžių pirkimą varpinės statybai.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Lunkevičius (Łunkiewicz), Jonas Liudvikas; Januškevičius, Jonas